2010
DOI: 10.1016/j.molcel.2010.10.018
|View full text |Cite
|
Sign up to set email alerts
|

WD40 Repeat Propellers Define a Ubiquitin-Binding Domain that Regulates Turnover of F Box Proteins

Abstract: SUMMARY WD40-repeat β-propellers are found in a wide range of proteins involved in distinct biological activities. We define a large subset of WD40 β-propellers as a class of ubiquitin-binding domains. Using the β-propeller from Doa1/Ufd3 as a paradigm, we find the conserved top surface of the Doa1 β-propeller binds the hydrophobic patch of ubiquitin centered on residues I44, L8, and V70. Mutations that disrupt ubiquitin binding abrogate Doa1 function, demonstrating the importance of this interaction. We furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
136
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(143 citation statements)
references
References 66 publications
7
136
0
Order By: Relevance
“…As in the absence of Ubc13/CHIP, where GHR is ubiquitinated to the same extent as in clathrin-depleted cells, it might indicate that Ubc13/CHIP might edit pre-existing, ␤TrCP-derived, ubiquitin chains on GHR. The opposite could be envisioned if we consider that the WD40 propeller domain of ␤TrCP was identified as a ubiquitin-binding domain, indicating that ␤TrCP might also recognize a ubiquitin moiety as its substrate (57). However, if we deplete CHIP, GHR is still ubiquitinated, presumably by ␤TrCP.…”
Section: Discussionmentioning
confidence: 89%
“…As in the absence of Ubc13/CHIP, where GHR is ubiquitinated to the same extent as in clathrin-depleted cells, it might indicate that Ubc13/CHIP might edit pre-existing, ␤TrCP-derived, ubiquitin chains on GHR. The opposite could be envisioned if we consider that the WD40 propeller domain of ␤TrCP was identified as a ubiquitin-binding domain, indicating that ␤TrCP might also recognize a ubiquitin moiety as its substrate (57). However, if we deplete CHIP, GHR is still ubiquitinated, presumably by ␤TrCP.…”
Section: Discussionmentioning
confidence: 89%
“…1 and 2). Accordingly, WD40 domains are known to bind ubiquitin (47), and notably, WD40 proteins are associated with more than a third of all DUBs (35). Various WD40 proteins have been shown to function as co-factors that stimulate the ubiquitin hydrolase activity of their cognate DUBs (48 -50).…”
Section: Discussionmentioning
confidence: 99%
“…Production of 13 C, 15 N -labeled NOD1 CARD for backbone assignments was done similarly to the 15 Nlabeled protein, except cells were resuspended in 13 C, 15 N-containing Celltone complete medium (100%). Production and purification of GST fusion proteins and MBP fusion proteins was performed according to standard protocols as described previously (31). GST-ATG16L1 WD40 was produced in MC1061 bacteria co-transformed with plasmid expressing GroES and GroEL as described previously (33).…”
Section: Methodsmentioning
confidence: 99%
“…1D). Previous experiments have shown that a wide variety of WD40 ␤-propellers are capable of binding Ub (31). We suspected the ␤-propeller of ATG16L1 might also have this activity and included this parameter in our experiments as a potential control for the validity of our binding experiments.…”
Section: Direct Interactions Of Nod1 Card With Rip2 Atg16l1 Andmentioning
confidence: 99%